Acute hormonal responses to high-intensity interval training in hyperoxia - Manferdelli, G.; Freitag, N.; Doma, K.; Hackney, A. C.; Predel, H. G.; Bloch, W.; Schumann, M. (Journal of Human Kinetics, 2020)
This study aimed to compare selected hormonal responses to a single session of high intensity interval training performed with an increased fraction of inspired oxygen (hyperoxia) and under normoxic conditions. Twelve recreationally trained men (age 24 ± 3 years) performed two sessions of high intensity interval training on a cycle ergometer, in randomized order with hyperoxia (4 L·min-1 with a flowrate of 94% O2) and normoxia. Each session consisted of 5 intervals of 3 minutes at 85% of the maximal power output, interspersed by 2 min at 40% of the maximal power output. Serum cortisol, prolactin and vascular endothelial growth factor (VEGF) were assessed both before and immediately after each high intensity interval training session. Statistically significant differences in cortisol were found between hyperoxic and normoxic conditions (p = 0.011), with a significant increase in hyperoxia (61.4 ± 73.2%, p = 0.013, ES = -1.03), but not in normoxia (-1.3 ± 33.5%, p > 0.05, ES = 0.1). Prolactin increased similarly in both hyperoxia (118.1 ± 145.1%, p = 0.019, ES = -0.99) and normoxia (62.14 ± 75.43%, p = 0.005, ES = -0.5). VEGF was not statistically altered in either of the conditions. Our findings indicate that a single session of high intensity interval training in low-dose hyperoxia significantly increased cortisol concentrations in recreationally trained individuals compared to normoxia, while the difference was smaller in prolactin and diminished in VEGF concentrations.